The Application of Ai-Based Audio-Visual Learning Media To Student Learning Interest In The Subject of Islamic Cultural History In Madrasah Ibtidaiyah - Mansur, Abu; Zuhdiyah, Zuhdiyah; Nurlaeli, Nurlaeli (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
In the digital era the learning process is directed to computerization such as the application of Competency-Based National Assessment (ANBK) all schools have implemented computerization as well as MI Azizan Palembang has started the learning process and assessment using computer media, the purpose of this study was carried out to determine the Application of Interactive Video Learning Media at Madrasah Ibtidaiyah Azizan, the Effect of Application of Interactive Video on Student Learning Interest, the research method in this study used an experimental method with a pre-test post test design, data collection techniques in this study using questionnaires, interviews and documentation, data analysis techniques carried out with simple linear regression. The research uses validity, reliability, and hypothesis testing, the results of the study, the learning process at MI Azizan has been running properly, from the results of the calculation of the simple regression test shows the significance value of 0.000 <0.05. so it can be concluded that the media used has a significant effect in developing students' learning interest. meaning that Ha which reads "audio-visual media has an effect on developing students' learning interest" has been proven. And from the output the R Square value is 0.915. This means that the effect of audio-visual media in developing students' interest in learning at MI Azizan Palembang is 91.5% and 8.5% is influenced by other variables not examined in this study.